The Influence of Content Authenticity, Online Review Quality, and Perceived Fairness on Digital Brand Trust in E-Commerce Applications in Indonesia - Rio Haribowo; Riesna Apramilda; Menhard; Apriani Riyanti; Ratu Nadya Wahyuningratna; Iwan Henri Kusnadi (Journal of Innovative and Creativity, 2025)
The primary purpose of this study is to investigate the impact that content authenticity, review quality, and perceived fairness have on trust in digital brands in Indonesian e-commerce applications. The rivalry in the e-commerce sector alongside the slow but steady rise in consumer trust in online transactions are the main backgrounds of the study. A quantitative explanatory approach has been utilized for the study, and 200 current users of e-commerce applications were selected as respondents through purposive sampling. The questionnaires made on a five-point Likert scale were the technique for collecting data and multiple linear regression was the method of analysis used. The research tool has successfully gone through the tests for validity, reliability, and other classical assumptions. The findings indicate that the three independent variables not only individually but also collectively have a significant and positive impact on the trust towards digital brands. Hence, the research has given a theoretical contribution to the literature on the evolution of digital brand trust in the e-commerce context. However, the implications of the research results are of a strategic nature and can be directed at the platform's managers, who in turn can strengthen user trust via, among other things, the use of authentic content, the application of effective review management, and the observance of fair and open policies.